FUNGSI KEPEMIMPINAN DALAM PENEMPATAN KERJA KARYAWAN PADA PT. HUMAN TECH INDONESIA - Ahmad Yani Kosali (Jurnal Bisnis Darmajaya, 2016)
This study was conducted to determine the function of leadership in the placement of employees at PT. Human Tech Indonesia, certainly needed a variety of instruments, ranging from infrastructure to the human resources, as well as the character of a leader. The character of a leader and a leader function itself is one of the main factors in the management of an organization, whether public or private. The method in this research is descriptive qualitative research method, where researchers collecting data obtained from sources are researched through observation, interviews, and documentation related to the title of the study. From the research, it is known that employees at PT. Human Tech Indonesia has been able to describe the policy given by the leadership in the form of a positive response to the duties and responsibilities given to them.Keywords: Overly protective, Expert, and Relevant